Transfer printing of fully formed thin‐film microscale GaAs lasers on silicon with a thermally conductive interface material. Issue 4 (29th May 2015) - Sheng, Xing; Robert, Cedric; Wang, Shuodao; Pakeltis, Grace; Corbett, Brian; Rogers, John A.
<x xml:space="preserve">Abstract</x> Fully formed thin‐film microscale GaAs based lasers are integrated onto silicon substrates using a transfer printing method. An indium‐silver alloy based adhesive layer serves as a thermally conductive interface. Experimental and numerical results demonstrate enhanced lasing performance due to advanced thermal management. The device integration strategies provide routes to on‐chip light sources for silicon photonics.